Improving Financial Literacy of Students: Specificity and Opportunities of Regional Higher Education Institutions - Semen D. Reznik; Olga A. Sazykina; Marina V. Chernikovskaya (National Research Mordova State University, 2023)
Introduction. Despite the significant measures and programs implemented by the countryʼs leadership to improve the financial literacy of the Russian population, students of Russian universities are still not financially literate enough. In this regard, it is necessary to develop and implement a set of intra-university educational practice-oriented technologies that can improve financial literacy and economic independence of students during the period of university education. The purpose of the article is to show the features and opportunities of regional universities of the country in solving the problem of improving financial literacy of student youth. Materials and Methods. The study of the problem of formation of financial literacy of student youth during university education was conducted on the basis of a questionnaire survey of 565 students from 29 universities of the Russian Federation in May‒June 2022 using a specially designed questionnaire via Google Forms. The results of the questionnaire survey were processed using the SPSS program and the method of comparative analysis of responses of students of leading (federal, national research, metropolitan) and regional Russian universities, which made it possible to identify and analyze the peculiarities of studentsʼ financial literacy formation depending on the status of their higher education institution Results. Self-assessment of students of regional universities of their financial literacy showed its low level, indicating the insufficiency or lack of serious knowledge in the financial sphere. At the same time, students understand the importance of financial literacy and indicate their willingness to participate in various forms of training on this issue. To implement the educational process aimed at intensive formation of studentsʼ financial literacy, the system of continuous practice-oriented formation of financial literacy is proposed. Discussion and Conclusion. The materials of the article can be useful in the organization of educational process in universities to improve financial literacy of students. In the future, the study will be supplemented by analyzing the formation of studentsʼ financial literacy at different stages of education on the basis of taking into account the influence of age, year of study and other factors.